THU0228 Validity of Omeract Preliminary Flare Questions in a Randomized Controlled Trial, that Assesses Impact of Disease Activity Guided Down-Titration of Anti-TNF Treatment in Rheumatoid Arthritis Patients in Low Disease Activity. (10th June 2014) - Van Der Maas, A.; van Herwaarden, N.; Woodworth, T.; Minten, M.; Furst, D.; Christensen, R.; den Broeder, A.; Choy, E.
Abstract : Background: The OMERACT RA flare group developed a preliminary set of questions to detect and measure flares in rheumatoid arthritis (RA) patients (preliminary flare questions, PFQs). Domains identified to potentially characterise key features of flare from patient's perspective include pain, function, fatigue, stiffness, participation, coping/self-management, patient report of number of swollen and tender joints. Previous analyses provided information on change for each question in patients recalling or reporting flare at the time of a planned visit [1, 2]. Here we report results for PFQs in patients in a randomised controlled trial (RCT) on tapering TNF-blockers vs usual care. Objectives: To examine OMERACT PFQs at baseline, and change in PFQs between visits without flares and between DAS28 based flare visit and preceding non-flare visit. Methods: RA patients treated with TNF-blockers for at least 6 months with DAS28 <3.2 and RA treatment for >6 months were included in an open RCT on tapering TNF-blockers vs usual care (Dose REduction Strategies of Subcutaneous TNF Inhibitors, DRESS study) [4]. In all patients, responses to PFQs and DAS28(CRP) were obtained at baseline and every 3 months. If patients thought they had a flare, an extra outpatient clinic visit was planned within 2 days. At each visit (regular/flare) the DAS28 based flare criterion (DAS28 >1.2, or >0.6 if DAS28 ≥3.2) was used to diagnose flare. PFQ responses are reported on a 0-10 numerical rating scale (NRS). Baseline data, change in PFQs between the first two visits in non-flaring patients and change in PFQs in flaring patients between the first DAS28 based flare visit and the preceding non-flare visits are described and tested. Results: 180 patients completed PFQs at baseline. Patients were mostly female (64%), rheumatoid factor and/or ACPA positive (81%), had established RA (median 10 yrs, [6-16.5]) and mean age was 59 years (sd10.1). Data on PFQ items at baseline, change between 1) first and second visit in non-flare patients and 2) flare visit and preceding non-flare visit in flare patients are described in table 1. In patients experiencing a DAS28 flare there is a statistical significant change in all items between flare and previous non-flare visit. There is no statistical significant change in items between visits in non-flaring patients, except for a small improvement in DAS28. Conclusions: In stable low disease activity patients, all PFQ items score low, including self-reported swollen and tender joint counts, with the exception of fatigue, which is still moderately present. In patients not experiencing a DAS28 based flare PFQ items do not change, whereas a statistical significant change is observed in patients experiencing their first DAS28 based flare. These findings provide further support for the construct and discriminatory validity of the OMERACT RA flare PFQs. References: Bykerk et al. ARD 2012;71(Suppl3):180 Bykerk et al. ARD 2012;71(Suppl3):509 Den Broeder et al. BMC Musculoskelet Disord. 2013 Oct 24;14(1):299 Van der Maas et al. ARD;72(11):1800-5 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2337